Efficient depolymerization of lignin through microwave-assisted Ru/C catalyst cooperated with metal chloride in methanol/formic acid media - Shao, Lupeng; Wang, Chao; Liu, Yu; Wang, Meng; Wang, Luyan; Xu, Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Lignin, an abundant aromatic biopolymer, has the potential to produce various biofuels and chemicals through biorefinery activities and is expected to benefit the future circular economy. Microwave-assisted efficient degradation of lignin in methanol/formic acid over Ru/C catalyst cooperated with metal chloride was investigated, concerning the effect of type and dosage of metal chloride, dosage of Ru/C, reaction temperature, and reaction time on depolymerized product yield and distribution. Results showed that 91.1 wt% yield of bio-oil including 13.4 wt% monomers was obtained under the optimum condition. Yields of guaiacol-type compounds and 2,3-dihydrobenzofuran were promoted in the presence of ZnCl2. Formic acid played two roles: (1) acid-catalyzed cleavage of linkages; (2) acted as an in-situ hydrogen donor for hydrodeoxygenation in the presence of Ru/C. A possible mechanism for lignin degradation was proposed. This work will provide a beneficial approach for efficient depolymerization of lignin and controllable product distribution.